2018
DOI: 10.1017/s1047951118000689
|View full text |Cite
|
Sign up to set email alerts
|

Incidental finding of pulmonary arterial sling during patent ductus arteriosus surgery in a patient with Mowat–Wilson syndrome

Abstract: Mowat-Wilson syndrome is a genetic condition due to a mutation in the ZEB2 gene; it affects many systems including the cardiovascular system. The pulmonary arterial sling originates from a failure of development of the proximal portion of the left sixth aortic arch, resulting in an anomalous left pulmonary artery origin from the posterior wall of the right pulmonary artery and the left pulmonary artery crossing to the left lung between the trachea and the oesophagus. We present a 4-month-old infant with Mowat-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…In addition, to ensure proper aortic arch development, E-cadherin signaling is required to be repressed by ZEB2 expression. This may represent the underlying pathophysiology of the cardiac anomalies commonly seen in MWS patients such as pulmonary artery sling and bicuspid aortic valve, which were also observed in affected individual 2 in the present study [Cano Sierra et al, 2018]. Considering all the anomalies involving the craniofacial skeleton, enteric ganglia, central nervous system, and aortic arches, it appears that MWS results from developmental defects of the neural crest cells and, therefore, is considered a neurocristopathy.…”
Section: Discussionsupporting
confidence: 62%
“…In addition, to ensure proper aortic arch development, E-cadherin signaling is required to be repressed by ZEB2 expression. This may represent the underlying pathophysiology of the cardiac anomalies commonly seen in MWS patients such as pulmonary artery sling and bicuspid aortic valve, which were also observed in affected individual 2 in the present study [Cano Sierra et al, 2018]. Considering all the anomalies involving the craniofacial skeleton, enteric ganglia, central nervous system, and aortic arches, it appears that MWS results from developmental defects of the neural crest cells and, therefore, is considered a neurocristopathy.…”
Section: Discussionsupporting
confidence: 62%
“…16 This highlights the utility of a wide-scope diagnostic test such as clinical exome in the setting of patients with developmental delay/intellectual disability and multiple congenital malformations, and adds MWS to the long list of potential differential diagnoses of NS and related RASopathies. 17 In Colombia, as far as we know, only four cases of MWS have been published, [18][19][20][21] from which, only one reported the genetic variant and it was a 2q22.32-q22.3 deletion, 19 including the KYNU, ARHGAP15, GTDC1 and ZEB2 genes. Hence, this is the first report of the c.2761C>T, (p.Arg921Ter) genetic variant in the country.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few reports have described the association of left pulmonary artery sling with chromosomal abnormalities, such as trisomy 18 10 and 21. 11 Recently, Cano Sierra et al 12 reported that pulmonary arterial sling is significantly more frequent in patients with Mowat-Wilson syndrome than in the general population. Mowat-Wilson syndrome, a multiple congenital anomaly/mental retardation syndrome, is a genetic condition due to a mutation in the Zinc finger E-box-binding homeobox 2 (ZEB2) gene, previously called ZFHX1B (SIP1) on chromosome 2.…”
Section: Discussionmentioning
confidence: 99%